(untitled) (Desarrollo, Estado y Espacio, 2025)
While English-speaking specialists in international relations use the word "power" to refer to both power and capacity ("le pouvoir et la puissance"), French political science distinguishes between them. The former refers to the actions of states within their sovereign territory, while the latter describes the capabilities they maintain in their relations with the outside world. While power immediately resonates with the issue of food—the need for food being at the heart of a country’s social contract—the association between food and power, with its connotation of extroversion, may seem less obvious, especially since power more readily rhymes with the military.